Dampak Iklan dan Promosi terhadap Keputusan Pembelian pada Marketplace Lazada - Muchammad Hamdani; Mujito Mujito; Mimin Rukmini; Didin Samsudin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of advertising and promotion on consumer purchasing decisions at Lazada online store. The type of research used is causal quantitative with the study conducted in Bogor City over six months (December 2019–May 2020). The population of this research is all Lazada consumers in Bogor, with an unknown total number, while the sample was taken using accidental sampling technique with 100 respondents. Data were analyzed using multiple linear regression. The results show that: (1) partially, advertising has a significant effect on purchasing decisions (tcount 7.423 > ttable 1.984; sig. 0.000 < 0.05), while promotion has no significant effect (tcount 1.718 < ttable 1.981; sig. 0.089 > 0.05); (2) simultaneously, advertising and promotion have a significant effect on purchasing decisions (Fcount 27.791 > Ftable 2.696; sig. 0.000 < 0.05); (3) the adjusted R² value is 0.351, indicating that 35.1% of purchasing decisions are influenced by advertising and promotion, while the remaining 64.9% are influenced by other factors not examined; (4) the most dominant variable is advertising, with a regression coefficient of 0.594.